Diachronic differences in literary representation of communication (based on the Russian and American short stories at the turn of the XIX–XX and the XX–XXI centuries) - Merchy, Aleksandra P. (Journal of the Belarusian State University. Philology, 2019)
Based on the material of the 24 Russian and American short stories separated by the XX century (approximately with the equal proportion of first-person and third-person narrative for two synchronous turns) it is analyzed the quantitative ratio of the following components of a text: the author’s narration, characters’ communication, represented in two forms: as direct speech and as narrator’s retelling (more or less compressed speech). It is determined that the average unit weight of a communicative component in the analyzed short stories represents some constant during the XX century and takes about a quarter of the volume of the text while the average unit weight of the direct speech in all the volume of communication is reduced by 1,5 % that shows the reduction of the depiction in representation of communication. In two chronological groups of the short stories the dispersion of the distinctions in unit weights of the communicative component increased significantly during the century: 11,1–70,5 % in the stories of the turn of the XIX–XX centuries and 9,2– 44,9 % in the texts of the turn of the XX–XXI centuries; it shows the increase of the variety of the short stories in the aspect of the representation of communication. In the analyzed stories with the first-person narrative the average unit weight of the direct speech as a part of a communicative component increased a little during the century (from 75,7 to 77,8 %): it is possible to observe the compensation of incompleteness of representation of communication in the compressed retelling by means of more concentrated depiction of some important scenes of characters’ communication in direct speech. In the stories with the third-person narrative the average unit weight of the compressed speech and the narration increased during the century: the authors represent the speech of the heroes more concisely, but interpret it more fully, neglecting the authenticity of the direct speech in representation of the heroes’ communication.